The Atlantic Meridional Overturning Circulation is not collapsing - Parker, Albert; Ollier, Clifford (Quaestiones Geographicae, 2021)
Boers (2021) wrote that, in the last century, the Atlantic Meridional Overturning Circulation (AMOC) may have evolved from relatively stable conditions to a point close to a critical transition. The claim is based on different AMOC indices, based on observational sea-surface temperature and salinity data from across the Atlantic Ocean basin. Boers’ conclusions (2021) are not based on systematic observations spanning the last and this century, but on subjective reconstructions of sea surface temperature and salinity, as accurate sea-surface and temperature data are only available over the last few decades. Additionally, the AMOC strength does not only correlate to sea surface temperature and salinity data. His as-sumption that the strength of the AMOC depends on poorly described sea-surface temperature and salinity only is not substantiated. The difficulties of estimating the sea surface temperature (SST) are highlighted in Chan et al. (2019). Even more difficult are the estimations of salinity.